2020
DOI: 10.1016/j.chemosphere.2020.127549
|View full text |Cite
|
Sign up to set email alerts
|

Removal of organic matter from wastewater reverse osmosis concentrate using granular activated carbon and anion exchange resin adsorbent columns in sequence

Abstract: Reverse osmosis concentrate (ROC) generated as a waste stream during reverse osmosis treatment of reclaimed wastewater, presents significant disposal challenges. This is because it causes environmental pollution when it is disposed to lands and natural water bodies. A long-term dynamic adsorption experiment was conducted by passing ROC from a wastewater reclamation plant, firstly through a granular activated carbon (GAC) column, and subsequently through an anion exchange resin (Purolite) column, for the remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Jamil et al [ 3 , 14 ] reported that the removal of DOC with GAC adsorption was larger compared to strong base anion exchange resins (Purolite ® A502PS, Purolite ® A860S). However, the anion exchange resins (AER) were found to remove more hydrophilic fractions selectively from DOC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jamil et al [ 3 , 14 ] reported that the removal of DOC with GAC adsorption was larger compared to strong base anion exchange resins (Purolite ® A502PS, Purolite ® A860S). However, the anion exchange resins (AER) were found to remove more hydrophilic fractions selectively from DOC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…GAC only achieved partial removal. A larger NOM removal resulted by combining the two adsorbents sequentially (GAC followed by Purolite) to take advantage of their different adsorbent affinities towards the range of NOM fractions present (Jamil et al 2020 ).…”
Section: Activated Carbon (Ac) and Ion Exchange Resin Adsorbentsmentioning
confidence: 99%
“…A study investigating NF brine treatment by other oxidational by oxidation. In a municipal application, RO brine treatment with GAC of a wastewater reclamation plant receiving biologically treated wastewater and stormwater was investigated by Jamil et al (2020) and nearly complete removal efficiencies (95-100%) for 17 micropollutants were achieved within 2,880 BVT treated.…”
Section: Micropollutant and Pathogen Removal By Hybrid Systems With N...mentioning
confidence: 99%